Direct and indirect effects of long‐term ditch‐buried straw return on soil bacterial community in a rice–wheat rotation system. (23rd December 2019) - Yang, Haishui; Meng, Yi; Feng, Jinxia; Li, Yifan; Zhai, Silong; Liu, Jian
Abstract: Ditch‐buried straw return (DB‐SR) is a novel soil tillage and fertility building practice that is effective in regulating soil carbon and nitrogen dynamics and hydrothermal processes in rice–wheat rotation systems. However, the effects of DB‐SR on soil bacterial community are still largely unclear. We deciphered soil bacterial community with high‐throughput sequencing under various returning approaches, burial depths, and straw amounts after 6.5 years of DB‐SR application. Our results showed that DB‐SR structured distinctive soil bacterial community with rotary tillage straw return (RT‐SR; one‐way analysis of similarities [ANOSIM]: P < .01). RT‐SR significantly reduced soil bacterial diversity by 3.87%, but DB‐SR could maintain it ( P > .05). These variations were mainly caused by water content‐driven changes in soil organic carbon. Also, bacterial community composition was distinctive among burial depth treatment (one‐way ANOSIM: P < .05), and deeper burial reduced species richness and diversity ( P < .05). Variation in C/N ratio could mostly explain the alterations in soil bacterial community structure under different burial depths. Moreover, the amount of straw buried had no significant effect on soil bacterial species richness or diversity ( P > .05), but bacterial community composition was more dissimilar with increasing straw amount (one‐way ANOSIM: P < .01). Our results suggest that long‐term DB‐SR can maintain the bacterial community structure in the surface soil layers when compared with conventional RT‐SR, but taking the current production level into consideration, the burial depth should not be greater than 20 cm for incorporating the full amounts of straws.